Foreign experience in state support for pig breeding development organizing and directions of its use in the domestic practice - Khakhula B. (Економіка та управління АПК, 2020)
The article is devoted to the study systematization of the directions of state support for pig production in the countries with intensive pig production which includes the following tools: subsidies, interest rate subsidies; research funding; insurance, preferential lending; compensation for material and production costs; price regulation; government interventions. It is established that state regulation in pigs breeding in the leading countries of the world is focused on ensuring intensive development of the industry, ensuring the animals productivity, as well as strict adherence to environmental requirements. World's leading producers tend to obtain lean pork due to consumer preferences which has led to a change in approaches in the entire production chain organization, from the revision of vectors of pigs breeding and feeding to technological innovations in the field of the processing, transportation and distribution. It was found out that the increase in pig production in the leading countries of the world is provided through the advances in animal breeding and genetics. Breeding programs of the world's leading countries are characterized by a tendency to consolidate breeding material in the global market of genetic resources, where pork production is innovative and integrated. Several multinational genetic companies dominate in the supply chain. Effective use of modern methods of animal reproduction makes it possible to store genetic material long-term and transport it to any place in the world, which enables to increase the sales of breeding products and inter-firm exchange of frozen sperm and embryos. The market of genetic resources is characterized by intensive trade and intensification of international competition between national breeding companies as well as the transition from national and regional breeding programs to the purchasing breeding material from multinational companies. Analysis of world experience in breeding programs and state support for pig breeding shows that the use of modern information technology and the development of information analytical support of breeding work with tribal recording as an important element can be the basic factors in accelerating the breeding process and increasing the efficiency of pig breeding in Ukraine.